An assessment of the knowledge management readiness of the benefits and gratuity claims unit of the AFP pension and gratuity management center with implications of implementing a knowledge management initiative - Agcaoili, Andrea Jessica E.; Dorado, Dan Anthony D. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2016)
The AFPPGMC, specifically the Benefits and Gratuity Claims Unit, handles hundreds of benefit claims cases every day. All sorts of documents and pertinent information are submitted to the unit and this can become overwhelming to manage. The BGCU administration may not be privy to the benefits of applying KM initiatives into their day to day processes because of gaps in the practices associated with managing knowledge assets.
The study aims to determine the readiness of the BGCU administration in adopting a knowledge management initiative through a KM audit. Through this, the BGCU administration can be gauged with how receptive they are to changes involving knowledge management. The research also aims to identify the factors that can influence the successful implementation of KM within the BGC, and recognize the KM tools that can help improve the current situation of the BGCU. The findings revealed that Information Technology is one factor that needs to be improved greatly if the BGCU is looking to adopt KM initiatives. The lack of proper IT platform for sharing knowledge and not knowing the knowledge needs of their colleagues are the top challenges in the BGCU which is rooted in their Organizational Culture. And although the BGCU is rich in knowledge gathered from documents and people alike, they are short on proper tools/technology and systems/processes to assist with documentation and storing information. The staff are in consensus that if more structured and regular modes of knowledge sharing were introduced in the BGCU, they are willing to support such initiatives.
Thesis (Bachelor of Library and Information Studies)--University of the Philippines Diliman
Keywords: Records management; Cost effectiveness